Ragi tapai and saccharomyces cerevisiae as potential coculture in viscous fermentation medium for ethanol production - Azmi, Azlin Suhaida; Ngoh, Gek Cheng; Mel, Maizirwan; Hasan, Masitah (Academic Journals, 2010)
A comparison study on the ethanol production from 20% (w/v) of unhydrolyzed raw cassava starch using Saccharomyces cerevisiae and Candida tropicalis was performed and compared with the commercialized ragi tapai. The findings showed that S. cerevisiae, C. tropicalis and ragi tapai produced 23, 20 mg/l and 26 g/l of ethanol in 72 h, respectively. Subsequent coculturing of the two best performing strains namely ragi tapai and S. cerevisiae were performed to improve ethanol production and to reduce the accumulation of inhibitory concentration of reducing sugar with 10% (w/v) unhydrolyzed raw cassava starch. The coculture of ragi tapai with S. cerevisiae using the unhydrolyzed raw starch in a single step-fermentation produced an ethanol concentration of 35 g/l when the starch was inoculated with ragi tapai and cocultured with S. cerevisiae. The yield was 46% higher than the one inoculated with ragi tapai only (24 g/l). The glucose concentration was maintained at a low concentration in the coculture medium as compared to the medium with pure ragi tapai. The findings suggested that coculture of ragi tapai with S. cerevisiae is capable of enhancing the ethanol production and prevention of the inhibitory effect of reducing sugars on amylolytic activity.